The mechanism of sevoflurane post-treatment alleviating hypoxic-ischemic encephalopathy by affecting histone methyltransferase G9a in rats. Issue 2 (20th December 2021) - Shan, Weifeng; Wu, Yini; Han, Xin; Chen, Qin; Wu, Jimin
ABSTRACT: Hypoxic-ischemic encephalopathy (HIE) is recognized as the main cause of neonatal death, and efficient treatment strategies remain limited. This study aims to investigate the mechanism of sevoflurane (SF) post-treatment in alleviating HIE in rats. The HIE rat model and oxygen-glucose deprivation (OGD) cell model were established, and adeno-associated virus (AAV)-histone-lysine N-methyltransferase EHMT2 (G9a) was transfected after SF treatment. The learning and memory ability and the levels of nerve growth factor (NGF)/brain-derived neurotrophic factor (BDNF) were evaluated and determined. The levels of G9a/histone H3 lysine 9 dimethylation (H3K9me2) and the enrichment level of H3K9me2 in the promoter region of BDNF gene were analyzed. After SF post-treatment, the neurons in cerebral cortex, the learning and memory skills and the contents of NGF/BDNF were increased, while the apoptosis and G9a/H3K9me2 levels were reduced. After overexpression of G9a in vitro/vivo, the enrichment levels of H3K9me2 in the promoter region of BDNF were increased, the levels of BDNF were decreased, the neurons were damaged and the learning and memory abilities of HIE rats were impaired. The conclusion is that SF post-treatment can promote the expression of BDNF by inhibiting H3K9me2 on the BDNF gene promoter and inhibiting G9a, thus alleviating HIE in rats.